On democracy - Dahl, Robert A.; Shapiro, Ian (Yale University Press, 2015)
This new edition includes two additional chapters by Ian Shapiro, Dahl's successor as Sterling Professor of Political Science at Yale and a leading contemporary authority on democracy. One chapter deals with the prospects for democracy in light of developments since the advent of the Arab spring in 2010. The other takes up the effects of inequality and money in politics on the quality of democracy, a subject that was of increasing concern to Dahl in his final years.